Understanding Political Reform and Islamic Education Position in Indonesia - Choirul Mahfud (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2020)
The political conditions in Indonesia which underwent a reformation in 1998 had an influence on position and the existence of Islamic education in Indonesia post-New order. In this era, the position of Islamic education is as a subsystem of national education. It cannot be separated from the changes in the education system regulation in this country, namely the National Education System regulation No. 2 1989 changed to Law of Sisdiknas No. 20 / 2003. These changes have a major impact on the progress and existence of Islamic education in Indonesia. This can be seen from the aspect of the authority of Islamic education which can actually be said to be the same as the policies in the previous legislation, namely in the education system, at least, there are still two ministries that manage educational institutions, namely the Ministry of Education and Culture (Kemdikbud) and the Ministry of Religious Affairs (Kemenag). Both institutions also organize education to tertiary level. In addition, there are basic, secondary, and tertiary education in the Ministry of Education and Culture, as well as the primary, intermediate, and tertiary education institutions administered by the Kemenag. This research intends to discuss the implications of political reform on the position of Islamic education in Indonesia.